FEASIBILITY STUDY (STUDI KELAYAKAN) PERENCANAAN PEMBANGUNAN TPS 3R DI PULAU SABIRA KABUPATEN KEPULAUAN SERIBU PROVINSI DKI JAKARTA) - Ernamaiyanti; Mega Yunanda (Jurnal Ilmiah BERING, 2022)
The purpose of this study was to compile a technical study of planning for the construction of 3R TPS on Sabira Island, Seribu Islands Regency, DKI Jakarta Province. The research method is a quantitative method. The types of surveys carried out are polygon and rate generation. The plan for the construction of the Sabira Island 3R TPS is recommended in an available location with a land area of ±375 m2 or 15 m x 25 m. The condition of Service and Waste Management on Sabira Island has a weighting score with a total score of 14. This means that the criteria for service and waste processing locations for the construction of 3R TPS on Sabira Island are recommended in the available locations. Of the four waste processing technologies on Sabira Island that were assessed using the SWOT method, it was concluded that composting was the one that exceeded the median score for both internal and external environmental factors. The number of collecting vehicles for motorbike carts on Sabira Island is 4 trips/day (1 (one) unit of existing motorbike cart is suitable for use). The loading rate to be processed at the 3R TPS on Sabira Island is 0.542 m3/hour. The land area required for the construction of the 3R TPS on Sabira Island is 193.67 m2. The social feasibility study in the plan for the construction of the 3R TPS on Sabira Island is that the people of Sabira Island support the plan for the construction of the 3R TPS. The service period of 3R TPS according to the technical analysis above is 10 years. Facilities and infrastructure are evaluated according to the applicable SNI standards in the current planning year.